Quo vadis, European Union? - Vladimir-Adrian Costea (CES Working Papers, 2019)
The general objective pursued through this research is to map out the main perspectives on the future of the European Union in the new legislature elected following the May 2019 elections, with regard to the main attitudes and preferences shaping the European citizens' agenda for the 2019 EU elections. We aim to illustrate and interpret the main trends at European and national level, providing a better understanding of how citizens relate to the main challenges faced by the European Union. The secondary objective of the research is to highlight the impact of the rise of populism and extremism on the results of the elections organized in the 28 Member States.
Keywords: 330; European elections; Eurobarometer Survey; European values; the Future of Europe; European crisis